Computation of the interpolation of two-dimensial splines of 3-th and 5-th orders - Plukas, Kostas (Lietuvos matematikos rinkinys, 1997)
Computation of the interpolation of two-dimensial splines of 3-th and 5-th orders, when splines are written as a linear combination of B-splines is discussed. The main attention is focused on the practical aspects of computation.